Informational Self-Determination and Patient Protection in AI-Assisted Healthcare: Ethical and Legal Perspectives - Hennessy, Rory Patrick (Trinity College Dublin. School of Law. Discipline of Law, 2025)
This study offers a doctrinal and socio-legal analysis of the emerging integration of Artificial Intelligence (AI) within European healthcare systems, with a central focus on protecting patient rights through the principle of informational self-determination. It begins by tracing AI’s development from its philosophical origins to contemporary societal and medical applications, highlighting its transformative and ethically disruptive potential. The work assesses the capacity of existing patient rights frameworks to respond to AI-related challenges, critically analysing informational self-determination as a means of safeguarding autonomy, privacy, equality, and safety. The final section evaluates emerging legislative responses - particularly the new EU Artificial Intelligence Act - identifying regulatory gaps and proposing enhanced governance mechanisms grounded in informational self-determination. The work concludes by advocating for an ethico-legal framework that centres this principle as essential to future AI governance in European healthcare.
APPROVED
Keywords: Artificial Intelligence; Informational Self-Determination; Healthcare; AI-Assisted Healthcare; Medical Law; Patient Rights; Medical Ethics; Autonomy; Informed Consent; Privacy; Human Rights; AI Regulation; EU Artificial Intelligence Act; General Data Protection Regulation; AI Ethics; Responsible Healthcare Innovation